2010
DOI: 10.1101/gad.552310
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylases 1 and 2 act in concert to promote the G1-to-S progression

Abstract: Histone deacetylases (HDACs) regulate gene expression by deacetylating histones and also modulate the acetylation of a number of nonhistone proteins, thus impinging on various cellular processes. Here, we analyzed the major class I enzymes HDAC1 and HDAC2 in primary mouse fibroblasts and in the B-cell lineage. Fibroblasts lacking both enzymes fail to proliferate in culture and exhibit a strong cell cycle block in the G1 phase that is associated with up-regulation of the CDK inhibitors p21 WAF1/CIP1 and p57 Kip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
307
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(340 citation statements)
references
References 44 publications
33
307
0
Order By: Relevance
“…Of note, HDAC1 was reported to antagonize p53 via Sp1 in regulating p21 transcription (45). Furthermore, HDAC1 and HDAC2 act in concert to repress the expression of p21 and p57 and promote G1 to S phase progression in mouse embryonic fibroblasts in vitro and B cells in vivo (46).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, HDAC1 was reported to antagonize p53 via Sp1 in regulating p21 transcription (45). Furthermore, HDAC1 and HDAC2 act in concert to repress the expression of p21 and p57 and promote G1 to S phase progression in mouse embryonic fibroblasts in vitro and B cells in vivo (46).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, loss-of-function studies in mice provide important insights regarding the compensatory functions of HDAC1 and HDAC2 in regulating cell proliferation, apoptosis, and differentiation in different cell types and tissues. 8,28 Tissue-specific conditional knockout of Hdac1 or Hdac2 alone does not evoke an obvious phenotype in cardiomyocytes, 29 neuron precursors, 30 oligodendrocyte, 31 B cells, 32 embryonic epidermis, 33 and T cells, 34 whereas deletion of both genes results in severe phenotypes in all tissues examined. In contrast, results of other studies support the notion that HDAC1 and HDAC2 have distinct functions.…”
Section: Structure and Complexes Of Mammalian Hdac1 And Hdac2mentioning
confidence: 99%
“…A similar situation is also observed recently in the developing nervous system, where a single allele of Hdac2, but not Hdac1, is sufficient for normal mouse brain development in the absence of its paralog. 38 Deletion of both Hdac1 and Hdac2 leads to DNA damage that ultimately results in apoptosis in a variety of cell types and tissues including B cells, 32 T cells, 34 thymocyte, 44 and brain. 38 A significant increased incidence of apoptosis accompanied by pronounced DNA damage is also observed in growing oocytes following loss of both Hdac1 and Hdac2 and likely attributed to hyperacetylation of TRP53.…”
Section: Hdac1 and Hdac2 Regulate Oocyte Development Through Transcrimentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence has demonstrated that epigenetic changes play a key role in shaping gene expression profiles of differentiating lymphocytes 12,13 . Similarly, mice deficient in histone deacetylase (HDAC) enzymes 1 and 2 have disrupted B-cell development, survival and activation [14][15][16] . Therefore, pharmacological targeting of epigenetic enzymes such as HDACs arises as a potential method for manipulating antibody responses.…”
mentioning
confidence: 99%